Problem-Based Learning dan Creative Thinking Skills Students Based on Local Wisdom in Maluku - Pamella Mercy Papilaya; Prelly Marsell J. Tuapattinaya (AL-ISHLAH: Jurnal Pendidikan, 2022)
In learning conservation biology with online learning communities, lecturers usually guide their students through a discussion-based learning process. In theory, mixed learning can increase interaction in the learning environment. Effective learning is promoted through flexibility, enabling the use of various student learning styles. This study aimed to 1) describe students' creative thinking skills about local wisdom on small islands in Maluku; 2) know the differences in creative thinking skills of experimental class students (using problem-based learning and conventional classes on small islands in Maluku; and 3) knowing differences in students' creative thinking skills on the topic of different local wisdom in small islands in Maluku. This research used the development of 4D Model teaching materials, field lectures, and online-based discussions. The data were analyzed descriptively, and the level of development of the 4D model combined with the student's PBL was evaluated using the normalized N-Gain g, while the quantitative data were analyzed through the ANCOVA test. The research findings reveal that competitive and facilitator styles significantly mediated the relationship between technology user acceptance and mixed learning on students' creative thinking skills. One of the weaknesses found in this study was the geographical differences between the islands. The internet facilities owned by students were not evenly distributed, and the needs of media were various. Blended learning was somewhat challenging to be applied in optimal learning. Scaffolding was given to students to concentrate more on education and independent activities. According to students, problem-based learning, creative thinking, finding information, and writing reports were problem-solving features that contributed the most to student learning.